The co-evolution of virtue and desert: debunking intuitions about intrinsic value. - Wiegman, Isaac; Dale, Michael T. (Synthese, 2024)
Thomas Hurka’s recursive account of value appeals to certain intuitions to expand the class of intrinsic values, placing concepts of virtue and desert within the realm of second and third order intrinsic goods, respectively. This is a formalization of a tradition of thought extending back to Aristotle and Kant via the British moralists, G. E. Moore, and W. D. Ross. However, the evidential status of such intuitions vis a vis the real, intrinsic value of virtue and desert is hostage to alternative explanations. If there is a plausible competing explanation for these intuitions, then the (putative) fact that desert and virtue are intrinsic (rather than instrumental or derivative) goods seems a much less obvious choice for the best explanation. As it turns out, there are plausible evolutionary explanations for these intuitions about desert and virtue. These evolutionary explanations suggest that it is adaptive to value desert and virtue separately from their instrumentality for other goods. Consequently, these explanations debunk intuitions about the intrinsic value of desert and virtue.